Effects of positional coracohumeral ligament stretching on the size of calcium deposits in adhesive capsulitis (Journal of Health Sciences, 2020)
Adhesive capsulitis is a painful condition of unknown etiology with restriction of active and passive movements of the glenohumeral joint. The condition is a result of inflammation, adherence, and swelling in the lining of the shoulder joint capsule and its associated ligaments, causing resultant contracture of the capsule. We describe a patient with calcified and thickened coracohumeral ligament with adhesive capsulitis and diabetes mellitus.